Melleron's Monsters - Hill, Douglas; Illustrated by Hutton, Steve (New York Oxford Press, 2000)
The story of a boy, Melleron, who meets Rose, the dragon, and Grit, the stone dog, who have come to the Peaceful Forest to escape from their sworn enemy, Horrimal - a huge monster with horns, yellow evil eyes, and a mouthful of fangs. But Horrimal and a wicked sorcerer are soon on their trail.
Include Illustration
Keywords: Readers (Elementary) -- Monsters -- Afrikaans language